Diversity-Oriented Synthesis and Optical Properties of Bichromophoric Pyrrole-Fluorophore Conjugates - Grotkopp, Oliver; Mayer, Bernhard; Müller, Thomas J. J. (Frontiers in Chemistry, 2018)
The mild reaction conditions of the palladium-copper coupling-isomerization reaction open a highly convergent, chromogenic route to blue emissive pyrroles in the sense of a consecutive four-component reaction. By virtue of this strategy a phenol derivative can be readily accessed, which can be transformed in a level-2 transformation to a library of bichromophoric pyrrol-fluorophore conjugates by facile alkylation with fluorophore halides. The photophysics of the underlying blue emitter derivative and the conjugates is studied by absorption and emission spectroscopy, furnishing intramolecular energy transfer at short distances as well as competing fluorescence quenching. In some cases partial energy transfer results in the occurrence of dual emission, for instance seen as magenta-rose emission arising from blue and red orange luminescence. The experimental photophysical studies are rationalized by DFT and TD-DFT calculations.